Managing the maturity structure of marketable treasury debt: 1953-1983 - Kenneth D. Garbade (Federal Reserve Bank of New York, 2020)
This paper examines the evolution of the maturity structure of marketable Treasury debt from 1953 to 1983. Average maturity contracted erratically from 1953 to 1960, expanded through mid-1965, contracted again through late 1975, and then expanded into the early 1980s. What accounts for these broad trends? In particular, what were the maturity objectives of Treasury debt managers? Were they able to achieve their objectives? Why or why not?
Keywords: G28; H63; N22; 330; Treasury debt management; maturity structure of debt; advance refundings